Catalytic Decarbonylation of Biosourced Substrates. Issue 9 (8th April 2015) - Ternel, Jérémy; Lebarbé, Thomas; Monflier, Eric; Hapiot, Frédéric
Abstract Linear α‐olefins (LAO) are one of the main targets in the field of surfactants, lubricants, and polymers. With the depletion of petroleum resources, the production of LAO from renewable feedstocks has gained increasing interest in recent years. In the present study, we demonstrated that Ir catalysts were suitable to decarbonylate a wide range of biosourced substrates under rather mild conditions (160 °C, 5 h reaction time) in the presence of potassium iodide and acetic anhydride. The resulting LAO were obtained with good conversion and selectivity provided that the purity of the substrate, the nature of the ligand, and the amounts of the additives were controlled accurately. The catalytic system could be recovered efficiently by using a Kugelrohr distillation apparatus and recycled.